Estudo sobre a temperatura no fresamento do aço ferramenta ABNT D2 empregando os métodos do termopar ferramenta/peça, termopar inserido e simulação numérica - Hugo Vilaça Lima (2017)
Machining performs a fundamental role in various branches of metal working industry. Among the machining processes, milling is one of the most important due to its metal remove rate and flexibility. Technological advances in tools and equipment make milling increasingly comprehensive and competitive, reaching ever tighter levels of dimensional tolerances, however temperature rise due to plastic deformation and friction between the chip and tool, and between workpiece and tool induces thermal damage and distortions which may impair the surface integrity of the part and accelerate tool wear rate. The purpose of this work is to present the construction and utilization of a measurement system consisting of a sensor, a data acquisition circuit, a microcontroller and a wireless transmitter. The need for wires between system and computer was eliminated by the use of a bluetooth module for the transmission of the collected data. This system was used to investigate the machining temperature under different cutting conditions when milling annealed ABNT D2 (180 HV) tool steel with coated tungsten carbide tools, using the tool/workpiece thermocouple method and the thermocouple implanted in the tool. Finally three-dimensional simulation of ABNT D2 steel milling was carried out in order to verify the evolution of the heat source on the tool wedge and to correlate the results with the experimental tests. The findings obtained using the tool/workpiece thermocouple method and the implanted thermocouple method indicate that temperature increased when cutting speed, feed rate, axial depth of cut and radial depth of cut were elevated. Based on the analysis of variance, cutting speed was the main parameter affecting milling temperature when the tool/workpiece thermocouple method was used, whereas the axial depth of cut was the principal parameter influencing milling when the implanted thermocouple method was used. The behavior of the cutting parameters showed the capacity of the system to respond to the variation of machining conditions. In addition, wear of the cutting edge caused an increase in the milling temperature; on the other hand, the change in tool coating had no significant effect on the milling temperature. The method developed to simulate the three dimensional milling temperature allowed to demonstrate the heat flux in the cut region and to correlate these results in a positive way with the values obtained in the experimental methods.